Integration of visible thinking routine in Nurul Fikri Islamic School as an effort to train thinking skills - R. Rahmat; Dinn Wahyudin; Laksmi Dewi (Research and Development in Education (RaDEn), 2025)
This study aimed to analyze the implementation of the Visible Thinking Routine (VTR) in Nurul Fikri Islamic School as an approach to training students' thinking skills. Using the survey research methodology, data were collected through observation, in-depth interviews with the science teacher population, and document analysis. The study's results stated that the use of VTR has a varied pattern, with a reasonably high adoption rate in Islamic Elementary School (IES) and Islamic High School (IHS) in certain months. At the same time, Islamic Middle School (IMS) recorded lower and consistent usage; IES was more active in implementing VTR in the last months, while IHS tended to be consistent throughout the month in this study. However, a significant issue in its implementation is the teacher's paradigm, which views the primary focus of learning as completing the subject matter, limiting the broader application of VTR as a tool for developing critical thinking skills. In addition, the biggest obstacle in implementation is the teacher's paradigm, which views the main focus of learning as completing the subject matter. VTR has a strategic role in training thinking skills and has yet to become the main focus of the learning process. This study recommends strengthening teacher training programs and integrating VTR into learning planning to improve teaching effectiveness in Islamic schools.